Palladium-coated kapton for use on dust detectors in low earth orbit: Performance under hypervelocity impact and atomic oxygen exposure - Dignam, Aishling; Wozniakiewicz, Penelope J.; Burchell, Mark J.; Alesbrook, Luke S.; Tighe, Adrian; Suliga, Agnieszka; Wessing, Johanna; Kearsley, Anton; Bridges, John; Holt, John; Howie, Stuart; Peatman, Libby; et al. (Frontiers in Space Technologies, 2022)
Observation of dust and debris in the near Earth environment is a field of great commercial and scientific interest, vital to maximising the operational and commercial life-cycle of satellites and reducing risk to increasing numbers of astronauts in Low Earth Orbit (LEO). To this end, monitoring and assessment of the flux of particles is of paramount importance to the space industry and wider socio-economic interests that depend upon data products/services from orbital infrastructure. We have designed a passive space dust detector to investigate the dust environment in LEO – the Orbital Debris Impact Experiment (ODIE). ODIE is designed for deployment in LEO for 1 year, whereupon it would be returned to Earth for analysis of impact features generated by dust particles. The design emphasises the ability to distinguish between the orbital debris (OD) relating to human space activity and the naturally occurring micrometeoroid (MM) population at millimetre to sub-millimetre scales. ODIE is comprised of multiple Kapton foils, which have shown great potential to effectively preserve details of the impacting particles’ size and chemistry, with residue chemistry being used to interpret an origin (OD vs. MM). LEO is a harsh environment – the highly erosive effects of atomic oxygen damage Kapton foil – requiring the use of a protective coating. Common coatings available for Kapton (e.g. Al, SiO2, etc.) are problematic for subsequent analysis and interpretation of OD vs MM origin, being a common elemental component of MM or OD, or having X-ray emission peaks overlapping with those of elements used to distinguish MM from OD. We thus propose palladium coatings as an alternative for this application. Here we report on the performance of palladium as a protective coating for a Kapton-based passive dust detector when exposed to atomic oxygen and impact. When subjected to impact, we observe that thicker coatings suffer delamination such that a coating of <50 nm is recommended. Analysis of atomic oxygen exposed samples shows a thin 10 nm coating of palladium significantly reduces the mass loss of Kapton, while coatings of 25 nm and over perform as well as or better than other commonly used coatings.